Comparative Study of the Use of HPA Lanolin and Breast Milk for Treating Pain Associated with Nipple Trauma - Mariani Neto, Corintio; de Albuquerque, Rosemeire Sartori; de Souza, Sonia Cristina; Giesta, Renata Oliveira; Fernandes, Andrea Penha Spinola; Mondin, Bárbara (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To compare two different treatments—the use of highly purified anhydrous (HPA) lanolin and expressed breast milk—for women with pain and nipple trauma during the breastfeeding process.Method A total of 180 puerperal women were randomly assigned to 2 groups: one was treated with HPA lanolin and the other with their own expressed breast milk. All of the participants received the same breastfeeding technique instructions and therapeutic care standard. Three assessments were performed: at the time of inclusion in the study (after randomization); after 48 hours; and after 7 days. At each interval, data was collected in relation to pain and trauma. A numerical/verbal category scale was used for the pain variable, and the nipple trauma score for the trauma variable. The results were subjected to statistical analysis using the chi-squared test, the Fisher exact test, the student t-test, and the Kolmogorov-Smirnov test. Generalized estimating equations were calculated using the STATA 12 statistical software package (StataCorp LLC, College Station, TX, USA) and IBM SPSS Statistics for Windows, Version 20.0 (IBM Corp, Armonk, NY, USA).Results There was pain improvement from the second to the third assessment in the group that used HPA lanolin, while the pain remained unchanged between these two periods (p < 0.001) in the breast milk group. In terms of trauma, improvement was identified in its extension and depth from the first to the third assessment, and it was higher in the HPA lanolin group than in the breast milk group (p = 0.025).Conclusion The treatment of pain and nipple trauma with HPA lanolin achieved better results than the one with breast milk, based on a 7-day treatment period.
Keywords: nipples/injuries; wound healing/drug effects; lanolin/therapeutic use; breastfeeding/adverse effects; breastfeeding/nipple pain